Effects of cohesive interfaces and polymer viscoelasticity on improving mechanical properties in an architectured composite. (1st March 2019) - Imam, Muhammed R.; Sain, Trisha
Abstract: Improving the functionality of composite materials is a key requirement for various aerospace, auto-motive, sports and defense applications. The trend is to identify mechanisms, design, constituents, and, preferably, the combination of all of them that can result into better mechanical properties in the conflicting domain of interest (e.g. high stiffness and high damping or high stiffness and high toughness) without adding much complexity in the analysis and design. In the present work, a naturally inspired "interconnection" is considered within a composite material made of dissimilar mechanical properties with an objective to improve stiffness, toughness, and wave attenuation capability. The computational study showed that creation of weak interfaces along with the "interconnection" works two-fold in terms of mechanical property improvement. The interconnection provides an additional load-transfer mechanism through contact-friction between two dissimilar materials, whereas the cohesive (weak) interfaces results in higher toughness (area under the stress-strain curve) of the material promoting distributed interface failure and delaying bulk material yielding. It was further identified that the presence of weak interfaces acts better in wave attenuation for the proposed composite.